A novel approach of hybrid guideline based on senior citizen online form design / Zanariah Idrus...[et al.] - Idrus, Zanariah; Abd Razak, Nor Hafizah; Abdul Talib, Noor Hasnita (2014)
The research focuses on the problems faced by the senior citizens during form filling process on web application services . By year 2020, The World Health Organization predicts the senior citizens population is more than 1 billion . They are progressively exposed to technology and to understand their requirements is significant in human interface design. Unfortunately , the online form interface design tends to ignore the issue of ease of use especially for senior citizens aged 55 and above. A well known Delivering Inclusive Access to Disabled and Elderly Members (DIADEM) guideline outlines the recommended online form design for the senior citizens. Recently, DIADEM guidelines were implemented in Europe and the results suggest that it is important as a reference for senior citizens ' online form design . But it is specifically tailored for senior citizens with age 65 and above only . WeFDeC guideline aligns the online form design based on the Three Layer Model (Perceptual , Conversational and Relationship layers). Though it is an acceptable guideline for online form but it does not take sen ior citizens into consideration . Therefore , this study will compare , identify the weakness and create a new hybrid model of DIADEM and WeFDeC guidelines. A new model (Elder-WeFDe) which should fit with senior citizens online forms applications and the Malaysian e-government online forms will be introduced . The methodology follows five phases ; identify the research problems, identify and compare the two guidelines, produce a new permutation model and test the model to the Malaysian e-government forms. A form from the current 1169 online forms in Malaysia e-government portal will be selected and tested to a randomly selected group of senior citizens aged 55 and above from Malaysia northern region .The expected outcome is a new hybrid model (Elder-WeFDe) to guide web or online form designers to design a better and ease of use on line forms applications for the senior citizens and all age of groups